Improving Speaking Sub-Skills by Using The Attention, Relevance, Confidence and Satisfaction (ARCS) Model - Junaidah Munawarah; Usman Kasim; Bukhari Daud (Universitas Syiah Kuala, 2018)
This research focussed on the use of the ARCS model to improve the speaking sub-skills of students. The sample for this research was 70 students in two groups; an Experimental Group (EG) and a Control Group (CG). The instruments used for collecting the data were tests (a pre-test and a post-test) and a questionnaire. The findings revealed that: (1) There was a significantly higher improvement in the scores of students who were taught using the ARCS model compared to the students who were taught using the Grammar Translation Method. The first hypothesis was proven by the z-test result (4.18); ie. That the difference was significant. The results from the data analysis proved that there were significantly better improvements in the post test scores of the EG, in terms of pronunciation, vocabulary, fluency and comprehension. The z-score for pronunciation was 3.29, grammar was 1.55, vocabulary was 2.35, fluency was 4.65 and comprehension was 2.25. Except for grammar, those z-scores were all outside the limits from -1.96 to +1.96. And (2) The results from the questionnaires showed the positive impact, viz: decrease in students’ nervousness plus enhancing students’ confidence and satisfaction in speaking in public.